PERAN KEPEMIMPINAN DALAM PEMBERDAYAAN TENAGA KEPENDIDIKAN - Muhammad Arbain (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2018)
Leadership is an important force in the effective management of managers. The essence of leadership is essentially the followership of the willingness of others or subordinates to follow the leader's wishes, that is what causes a person to become a leader. In other words, the leader will not be formed if there are no subordinates. The success of a school or madrasah lies in the efficiency and effectiveness of the appearanceof a principal or a madrasah. Yukl categorizes the success of the principal is always emphasized on three basic skills that need to have, namely: technical skills, interpersonal skills, and conceptual skills.Efforts made by the principal in improving the quality of human resources, especially in improving the performance of educational personnelis to include teachers in upgrading activities, seminars, workshops, or trainings that can provide additional knowledge of teachers' knowledge. Likewise with the staff at the educational institutions are given various training how to plan, implement, and evaluate the activities of administration in educational institutions. With the various efforts of the principal in improving the professionalism of educational personnel performance, it is expected that the quality of educational institutions can be more excellent and always experience improvement continuously (kaizen) and can be competitive.